Globalized Eating Cultures Mediation and Mediatization - Dürrschmidt, Jörg; Kautt, York (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This innovative volume explores the link between local and regional eating cultures and their mediatization via transnational TV cooking shows, glocal food advertising and social media transfer of recipes. Pursuing a global and interdisciplinary approach, it brings together research conducted in Latin America, Australia, Africa, Asia and Europe, from leading scholars in sociology and political science, media and cultural studies, as well as anthropology. Drawing on this rich case study material facilitates a revealing and engaging analysis of the connection between the meta-concepts of globalization and mediatization. Across fifteen chapters its authors provide fresh insights into the different impact that food and eating cultures can have on the everyday mediation of ethnicity and class as well as local, regional and transnational modes of belonging in a media rich global environment. This exciting addition to the food studies literature will appeal in particular to students and scholars of sociology, anthropology, media and cultural studies.